Improved outcomes of major laparoscopic liver resection for hepatocellular carcinoma. (December 2020) - Kim, Hyo Jun; Cho, Jai Young; Han, Ho-Seong; Yoon, Yoo-Seok; Lee, Hae Won; Lee, Jun Suh; Lee, Boram; Kim, Junyub
Abstract: Background: Minor laparoscopic liver resection (LLR) is currently becoming standard treatment option for hepatocellular carcinoma (HCC) while major LLR is still challenging. Recent advancement of surgical techniques has enabled surgeons to perform major LLR. This study compared the outcomes of major LLR for HCC before and after the adaptation of technological improvements. Methods: We retrospectively analyzed 141 patients who underwent major LLR for HCC from January 2004 to July 2018.32 open conversion cases were excluded. We divided the patients into two groups according to the date of operation: Group 1 (n = 38) and Group 2 (n = 71) who underwent major LLR before and after 2012, when advanced techniques including the use of intercostal trocars, Pringle maneuver, and semi-lateral position of patient were introduced. We also compared these patients including open conversion cases (n = 141) with those who underwent major open liver resection (OLR; n = 131) during the same period. Results: Mean operative time (413.0 min vs 331.0 min; P = 0.009), transfusion rate (31.6% vs 11.3%, P = 0.009) and hospital stay (9.8 days vs 8.5 days; P = 0.001) were significantly less in Group 2. Intraoperative blood loss (1269.7 ml vs 844.5 ml; P = 0.341) and postoperative complication (15.8% vs 23.9%; P = 0.320) were not significantly different between the groups. Although tumor size in OLR group and type of resection was different, transfusion rate (36.6% vs 24.1%; P = 0.026), postoperative complication (41.2% vs 25.5%; P = 0.007), and hospital stay (17.2 days vs 10.0 days; P < 0.001) were significantly lower in LLR group. Conclusion: Development of surgical techniques have gradually improved the surgical outcomes of the laparoscopic major liver resection. Highlights: Laparoscopic operation for major liver resection is technically demanding. Advancement of surgical techniques have improved surgical outcomes of laparoscopic major liver resection. Compared with open resection, laparoscopic major liver resection showed lower complication rate and shorter hospital days. 5-year survival rate and disease-free survival rate were superior for laparoscopic liver resection group.